A comparative study on acoustical properties using waste recycled porous materials for environmental sustainability - Vinoth Kumar Selvaraj; Jeyanthi Subramanian; Sri Sai Dutt; K. Annamalai; Elango Natarajan; S. Kumaresan (Scientific Reports)
Abstract As noise pollution intensifies in urban areas, the need for sustainable and effective sound-reducing porous materials becomes increasingly critical. This research addresses that need by developing gypsum-based composites enhanced with vermiculite and recycled rigid polyurethane (RPU) powder, using a blend-press-sinter methodology. Gypsum-based composites were chosen for their cost-effectiveness, recyclability, structural stability, and sound-absorbing properties, all with minimal environmental impact. This approach supports the circular economy by repurposing waste materials. High-resolution scanning electron microscopy (HR-SEM) and Fourier transform infrared spectroscopy (FTIR) were employed to analyze the size, structure, uniformity, and presence of organic and inorganic compounds. Using response surface methodology (RSM) for optimization, the ideal formulation for the noise reduction coefficient (NRC) was identified, with an optimal mix of 5.3 wt% vermiculite and 6.5 wt% RPU, achieving an NRC value of 0.3628. Acoustic simulations using COMSOL Multiphysics, guided by the Johnson-Allard model, demonstrated that the optimized composite effectively reduced sound pressure levels by 17 to 58 dB across the 200 to 2000 Hz frequency range. These findings underscore the composite’s potential for room acoustics applications. By incorporating recycled and natural materials, this approach not only enhances acoustic performance but also promotes sustainable material practices.